Scale insects (Hemiptera: Coccomorpha) on sugarcane in Colombia, with description of a new species of Tillancoccus Ben-Dov (Coccidae) - Caballero, Alejandro; Ramos-Portilla, Andrea Amalia; Kondo, Takumasa (Zootaxa, 2017)
Herein we describe a new species, Tillancoccus koreguajae Caballero & Ramos, sp. n. (Hemiptera: Coccidae) from Colombia collected on sugarcane. Pinnaspis strachani (Cooley) is also recorded on sugarcane for the first time worldwide. An updated list of seven species of Coccomorpha on sugarcane in Colombia is provided, including information on its distribution, biology, and mutualistic ants for each species. Seven species of scale insects (Hemiptera: Coccomorpha) have been recorded previously on sugarcane, Saccharum officinarum L. (Poaceae) in Colombia: Pseudococcidae: Dysmicoccus boninsis (Kuwana), D. brevipes (Cockerell), Pseudococcus calceolariae (Maskell), Saccharicoccus sacchari (Cockerell); Coccidae: Pulvinaria elongata Newstead; Diaspididae: Duplachionaspis divergens (Green) and Serenaspis minima (Maskell). However, the record of S. minima in Colombia is considered doubtful as there are no voucher specimens from Colombia and because the distribution of this species is currently limited to the Australasian region. Pseudococcus calceolariae is present in Colombia but its record on sugarcane is also doubtful. A taxonomic key for the identification of scale insects on sugarcane in Colombia is provided.